GENETIC CHARACTERIZATION OF LONGTAIL TUNA Thunnus tonggol (BLEEKER, 1851) BASED ON PARTIAL SEQUENCE OF 16S rRNA MITOCHONDRIAL GENE - Achmad Zamroni; Suwarso Suwarso; Arif Wibowo (Indonesian Fisheries Research Journal, 2018)
Although the Longtail tuna (Thunnus tonggol) is an important fish in Indonesia, the population structure has not been investigated. In this study, the genetic differences in geographic scale are analyzed to provide a clear picture of the structure of T. tonggol populations along a transect stretching from Pemangkat (western Kalimantan) to Pekalongan in the Java Sea. We also analyzed SNPs in the mitochondrial 16S rRNA gene of T. tonggol as potential molecular marker for the identification of the origin within species. In total, three polymorphic sites (all represent singleton dimensions) were identified in the sequence analysis of the 570-bp fragment among a total of 97 T. tonggol individuals from Pekalongan and Pemangkat. Based on these polymorphic sites, four haplotypes were identified. The Pemangkat samples had higher amount of haplotype and nucleotide diversity (h = 0.1556 ± 0.0680 and  = 0.000277 ± 0.000432), meanwhile samples Pekalongan showed lower levels of diversity (h = 0.0400 ± 0.0380 and  = 0.000070 ± 0.000209). The study revealed a single, intermixing population of T. tonggol across the sampled location. No significant structuring was observed between other pairwise comparisons, indicating gene flow between geographically adjacent locations.